PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GAME EDUKASI DIGITAL PADA MATERI RANTAI MAKANAN TERHADAP LITERASI DIGITAL SISWA KELAS V SD - endin; Juli Firmansyah; Amprasto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to examine the differences in digital literacy between 5th grade students of SDN 1 Mekarjaya who are taught with Problem Based Learning (PBL) assisted by digital educational games and expository models on food chain material. Using a quasi-experimental method, two classes were sampled: the experimental class (PBL with educational games) and the control class (expository), each with 28 students. Each class was given a pretest and posttest. The instruments used were document studies and tests. The test was used to determine students' digital literacy. The results of data processing showed the calculation of the average pretest value of the experimental class of 4.77 and the control class of 3.75. Because the average pretest of the experimental class and the control class were different, the posttest results were no longer compared to find differences in digital literacy between the experimental class and the control class. The data from the research were then tested with an N-gain test to analyze whether there was an increase in digital literacy from learning outcomes in the experimental class and the control class. The results showed a significant increase in digital literacy in both groups after learning. However, PBL assisted by digital educational games proved to be more effective in improving students' digital literacy compared to the expository model. Thus, the use of PBL assisted by digital educational games has a positive effect on students' digital literacy in the food chain material.